America's financial crisis: The end of an era - Barry Bosworth; Aaron Flaaen (Asian Development Bank Institute (ADBI), 2009)
This paper reviews research on the origins of the financial crisis of 2008-2009, highlights the key events that triggered a financial panic in September 2008, and summarizes the extraordinary policy actions the United States (US) has taken to ameliorate the crisis. We discuss the proximate causes of the crisis, including the characteristics and growth of the subprime mortgage market, and the distorted incentives and flawed regulatory structure surrounding the secondary market for mortgage-backed securities. We also assess the role of more fundamental macroeconomic determinants of the bubble in US asset prices, most notably low global interest rates attributed to either loose monetary policy or excess global saving. We find that while low global interest rates may have contributed to the boom in housing markets and speculative excesses, the poorly understood innovations and microeconomic distortions of the financial system played a more fundamental role. Finally, the otherwise extraordinary policy response of the US government has been limited by the lack of an effective restructuring of the financial system, and a recovery marked by higher private saving, weak domestic investment, and a large public deficit appears to be unsustainable. Ultimately, the US economy will need to shift about 3% of GDP from domestic consumption to the export sector. This will pose some serious challenges to countries that have come to rely on exports to the US market.
Keywords: G01; E65; E66; E69; F40; 330